Psikoedukasi mengenai Kecemasan dalam Pembelajaran Daring Selama Pandemi Covid-19 - Olivianty Saputri; Saphira Salsabilah Syamsuddin; Satifah Cahyani; Ismalandari Ismail; Ahmad Ridfah (IPTEK: Jurnal Hasil Pengabdian kepada Masyarakat, 2022)
Abstract. This prevention is carried out to provide information, knowledge and education to students so that they can overcome or prevent anxiety experienced during online learning. The subjects in this prevention were students and student(i) as many as 154 people. Based on a survey conducted through Google Forms, it was found that the subjects liked the appearance of the psychoeducational posters that had been distributed, and understood the content of the posters that had been distributed. Most of the subjects felt that the prevention posters were useful and provided sufficient information related to anxiety in online learning during the COVID-19 pandemic. The subject's response to the poster and its contents is that the poster is interesting and easy to understandKeywords: anxiety, prevention, psychoeducation